Sandwich-structured graphite-metallic silicon@C nanocomposites for Li-ion batteries. (10th February 2016) - Sun, Zixu; Wang, Guangjin; Cai, Tingwei; Ying, Hangjun; Han, Wei-Qiang
Graphical abstract: Abstract: In this work, we synthesize a sandwich-structured graphite-metallic silicon@C (MS-G@C) composite, which shows good electrochemical performance compared to metallic silicon or graphite-metallic silicon. The improved electrochemical performance may be ascribed to the sandwich structure of the composite with the carbon coating on metallic Si and to the metallic Si particles with high electronic conductivity according to the results of four probe tester measurement and a density functional theory study. When evaluated as an anode material for LIBs, the low cost MS-G@C anodes Exhibit 830 mA h g −1 at 0.5 C, 650 mA h g −1 at 1 C, and 251.2 mA h g −1 at 5 C, respectively, and after 100 cycles with an average capacity loss of only 0.02% per cycle at 0.5 C. The synthetic method presented in this paper is provided a facile and low-cost strategy for the large-scale production of silicon-based material as an anode in LIBs.